Gene flow and diversification in a species complex of Alcantarea inselberg bromeliads - Lexer, Christian; Marthaler, Fabienne; Humbert, Sarah; Barbará, Thelma; Harpe, Marylaure; Bossolini, Eligio; Paris, Margot; Martinelli, Gustavo; Versieux, Leonardo M. (Botanical journal of the Linnean Society, 2016)
Inselberg‐adapted species of bromeliads (Bromeliaceae) have been suggested as model systems for understanding the evolutionary genetics of species complexes and radiations in terrestrial, island‐like environments. Bromeliads are particularly suitable for addressing the potential roles of interspecific gene exchange during plant speciation and radiation. We have studied populations of five narrowly endemic Alcantarea species adapted to high‐elevation inselbergs of the Atlantic Rainforest of Brazil with nuclear and plastid DNA markers, estimated outcrossing rates in the giant bromeliad A. imperialis using progeny arrays and carried out a pilot study on the use of next generation sequencing‐based genotyping in this group. Our results suggest widespread and asymmetric interspecific gene flow in the studied species complex, which visibly affects patterns of genetic diversity in the phenotypically variable mixed outcrosser A. imperialis. Our data support the hypothesis that gene flow has contributed to the origin of phenotypic forms in the A. imperialis s.l. species complex. We discuss potential conflicts between our neutral marker data and previous taxonomic work and suggest how these might be resolved. We close with a brief outlook on the potential of genomic tools to uncover the hidden links between genotypes, phenotypes and niches in bromeliads and other plant radiations.